2020
DOI: 10.1007/s13318-020-00652-2
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Pharmacokinetics of RIPK1 Inhibitor GSK2982772 in Healthy Western and Japanese Subjects

Abstract: Background and Objectives GSK2982772 is an oral small-molecule RIPK1 inhibitor with potential therapeutic efficacy in immune-mediated inflammatory diseases (IMIDs). An inter-ethnic comparison of GSK2982772 pharmacokinetics was conducted based on data from Western (Study 1) and Japanese subjects (Study 2). Methods Both studies were single-centre, randomised, double-blind, placebo-controlled studies with objectives to assess the safety and characterise the pharmacokinetic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 15 publications
0
7
0
Order By: Relevance
“…Taken together, these results do not support the notion that RIPK1 inhibition alone at the level achieved in this study could translate into transformative improvement of UC. 27–29 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Taken together, these results do not support the notion that RIPK1 inhibition alone at the level achieved in this study could translate into transformative improvement of UC. 27–29 …”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these results do not support the notion that RIPK1 inhibition alone at the level achieved in this study could translate into transformative improvement of UC. [27][28][29] Other limitations to the study include the relatively small sample size and that baseline information regarding disease severity, including Montreal classification, was not collected. The impact of disease heterogeneity between treatment groups may have affected outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…GSK2982772 is a RIPK1 inhibitor. The first-in-human study showed that single and repeat doses of GSK2982772 were generally safe and well-tolerated in healthy adult volunteers, which support progression into Phase II clinical trials (Weisel et al, 2017;Tompson et al, 2021). The phase 2a clinical trials showed a certain therapeutic effect on active plaque psoriasis, and other phase 2a clinical trials in moderate to severe psoriasis are currently underway (Weisel et al, 2020).…”
Section: Opportunities For Therapymentioning
confidence: 76%
“…GSK2982772 is considered a Biopharmaceutics Classification System (BCS) class 2 drug substance characterized by high passive permeability (human Peff [effective permeability] > 2 × 10 -4 cm/s), and low solubility (0.1 mg/mL) (9,10). Despite the low solubility, when GSK2982772 is administered either as standard immediate-release (IR) tablets or powder in capsules, there is no evidence of dissolution rate-limiting absorption up to a dose of 240 mg (11). Median time to maximum concentration (T max ) is approximately 2 h post-dose (8).…”
Section: Introductionmentioning
confidence: 99%